Links between adolescent athletes` prosocial behavior and relationship with parents: A Mixed methods study - Lisinskiene, A.; Lochbaum, M. (Sports, 2018)
Adolescent relationships with parents are of the highest importance. The relationships likely reflect the nature of internal working models in youth sport that may well function as a psychological template during the construction of youth prosocial behavior. However, researchers` focus to date has concerned specific aspects of parental practices in child-based sporting activities. There is a lack of research covering parent-athlete interpersonal relationships concerned with how the relationships affect adolescent prosocial behavior. The purpose of this mixed methods explanatory sequential study was to examine teenage athletes` prosocial behavior and their relationships with parents. To achieve our purpose, we obtained quantitative data from 1348 athletes and non-athletes (ages 12-16), and qualitative data from 12 adolescent athletes and 12 youth sports parents. In the quantitative phase, we assessed adolescent prosocial behavior regarding the following six forms of prosocial behavior: public, anonymous, dire, compliant, altruistic and emotional. In the qualitative follow-up, three themes emerged from the adolescent athlete`s perspective: (1) sport as an escape; (2) parent-child relationships in youth sports; (3) adolescents` desired behavior. Three themes emerged from the parental perspective: (1) sport as protection and as a school of life; (2) painful decisions to release a child; (3) understanding adolescent behavior. We found protection from delinquent behavior and increased prosocial behavior with securely attached young athletes who are actively involved in sports